Lifting vs volumizing—The difference in facial minimally invasive procedures when respecting the line of ligaments. (12th August 2019) - Casabona, Gabriela; Frank, Konstantin; Koban, Konstantin C.; Freytag, David L.; Schenck, Thilo L.; Lachman, Nirusha; Green, Jeremy B.; Toni, Sabiha; Rudolph, Christina; Cotofana, Sebastian
Abstract: Background: The arrangement of the facial soft tissue layers is different with respect to the line of ligaments: medially oblique and laterally in parallel. Aims: This split‐face study was designed to investigate the effects on midfacial volumization if the same medial vs lateral injection points are targeted in various sequences. Methods: Twelve patients (3 males, 9 females; 46.67 years ± 4.5) were included in this interventional study. On the right side of the face, lateral injection points were performed first, whereas on the left side, medial injection points were executed first. The infraorbital hollowness score, the upper cheek fullness score, the global aesthetic improvement scale, and the injected volume were assessed. Results: No side differences were observed after the intervention with P = 1.00 for all scores. When the lateral injection points were performed first, the volume injected into the medially located injection points (0.46 ± 0.26 cc vs 0.73 ± 0.31 cc [ P = .037]), into the lateral injection points (0.79 ± 0.40 cc vs 1.15 ± 0.28 cc [ P = .017]), and overall (1.26 ± 0.64 cc vs 1.88 ± 0.57 cc [ P = .02]) was significantly reduced. Conclusion: The results of the present study emphasize the importance of respecting the layered arrangement of the facial soft tissues when performing minimally invasive soft tissue filler injections. Targeting injection points lateral to the line of ligaments first reduces the volume needed to symmetrically and aesthetically appealing manner and volumizes the infraorbital and upper cheek regions.